Icariside II-induced mitochondrion and lysosome mediated apoptosis is counterbalanced by an autophagic salvage response in hepatoblastoma. Issue 1 (28th September 2015) - Geng, Ya-di; Zhang, Chao; Shi, Ya-min; Xia, Yuan-zheng; Guo, Chao; Yang, Lei; Kong, Ling-yi
Highlights IS induces apoptosis through mitochondrial and lysosomal membrane permeabilization in HepG2 cells. Impairs autophagosome degradation is involved in IS-induced autophagosome accumulation in HepG2 cells. IS-induced autophagosome accumulation plays a pro-survival role through engulfing dysfunctional lysosomes and mitochondria. IS exhibits anti-tumor effect in mice transplanted with H22 liver carcinomas with the same mechanism as in vitro.